2006
DOI: 10.1016/j.micres.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of laccase gene expression during degradation of 2,4,6-trinitrotoluene and its catabolic intermediates in Trametes versicolor

Abstract: We have cloned a laccase gene fragment isolated from a Trametes versicolor strain in Korea. It showed high similarity in nucleotide sequences when compared with other fungal laccases. TNT (2,4,6-trinitrotoluene), a widely used explosive, was transformed rapidly by T. versicolor. When TNT and its catabolic intermediates were added to the fungal culture, they were transformed during the first few hours and the expression level of the laccase gene was increased during the early stage of cultivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
0
30
0
1
Order By: Relevance
“…2), but MnP and LiP activities were not detected throughout the treatment period (data not shown). Recent studies demonstrated that the expression of laccase gene from T. versicolor is increased under degrading conditions for 2,4,6-trinitrotoluene, BPA, NP, and two phthalic esters (Cheong et al 2006;Kim et al 2008). In the present study, the laccase gene expression during the degradation of iso-BP was not examined, but the data on enzyme production shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2), but MnP and LiP activities were not detected throughout the treatment period (data not shown). Recent studies demonstrated that the expression of laccase gene from T. versicolor is increased under degrading conditions for 2,4,6-trinitrotoluene, BPA, NP, and two phthalic esters (Cheong et al 2006;Kim et al 2008). In the present study, the laccase gene expression during the degradation of iso-BP was not examined, but the data on enzyme production shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These enzymes are also involved in the degradations of many recalcitrant chemicals such as dye (Faraco et al 2009), EDCs (Cabana et al 2007;Asgher et al 2008), explosives (Cheong et al 2006) and pesticides (Maruyama et al 2006;Rezende et al 2005). We have isolated many white rot fungi to examine their degrading activities against dyes, EDCs and other recalcitrant compounds such as polyaromatic hydrocarbons, and several fungi were selected by their degrading abilities against recalcitrant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…리그닌을 분해하는 백색부후균류는 분해 에 필요한 효소를 가지고 있는데, laccase, lignin peroxidase 및 manganese peroxidase 등이 보고되었다. 이 효소들은 기질특이 성이 강하지 않기 때문에 폭약류 (Cheong et al, 2006), 내분비계 장애물질 Yeo et al, 2008)과 다양한 난분해성 물질(Baldrin, 2006)을 분해한다고 보고되었다. 경기도 광릉의 숲에서 분리한 아교버섯은 다양한 내분비계 장애물질을 더한 potato dextrose 한천배지에서 잘 생장하였기 때문에 이 균이 가 지고 있는 리그닌 분해효소들에 대하여 연구를 수행하였다.…”
unclassified